2017
DOI: 10.3892/etm.2017.5525
|View full text |Cite
|
Sign up to set email alerts
|

Clipping treatment of posterior communicating artery aneurysms associated with arteriosclerosis and calcification: A single center study of 136�cases

Abstract: Abstract. It is widely acknowledged that arteriosclerosis and calcification of the parent artery and aneurysm neck make it difficult to clip posterior communicating artery (PCoA) aneurysms. A total of 136 cases of PCoA aneurysms accompanied by arteriosclerosis and calcification were collected and treated with clipping in the present study. Of the 136 patients, 112 were females (82.4%) and 24 were males (17.6%), with ages ranging from 37 to 76 years (mean age, 60.2 years). Rupture of a PCoA aneurysm was identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Very few studies mention the ischemic complications associated with the same. [15][16][17][18][19][20] Aoki et al [2] reported a favorable outcome of 79% in the form of no fresh deficits in a retrospective study of 50 patients in Japan who underwent surgical clipping or coiling for incidental IC PC aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…Very few studies mention the ischemic complications associated with the same. [15][16][17][18][19][20] Aoki et al [2] reported a favorable outcome of 79% in the form of no fresh deficits in a retrospective study of 50 patients in Japan who underwent surgical clipping or coiling for incidental IC PC aneurysms.…”
Section: Discussionmentioning
confidence: 99%